2019
DOI: 10.1177/0306624x19861052
|View full text |Cite
|
Sign up to set email alerts
|

Futurelessness, Risk Perceptions, and Commitment to Institutional Rules Among a Sample of Incarcerated Men and Women

Abstract: Using self-reported surveys of a sample of 2,927 incarcerated men and women from correctional facilities of varying security levels in the United States, this study explores the interrelationship of futurelessness, perceived certainty and celerity of punishment, and commitment to institutional rules. Incarcerated individuals’ commitment to rules with an adult sample has not been explored with consideration to emotionality. Findings suggest that futurelessness and risk perceptions are directly and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Commitment to institutional rules. Consistent with prior work (Abderhalden et al, 2020), the measure of commitment to institutional rules is made up of a three-item mean standardized index. This involves standardizing each item by subtracting the mean of that item from each individual response then taking the arithmetic mean of the three items by adding them together and dividing by the number of items.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Commitment to institutional rules. Consistent with prior work (Abderhalden et al, 2020), the measure of commitment to institutional rules is made up of a three-item mean standardized index. This involves standardizing each item by subtracting the mean of that item from each individual response then taking the arithmetic mean of the three items by adding them together and dividing by the number of items.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps most relevant to the present study, Abderhalden et al (2020) examined futurelessness in relation to commitment to follow institutional rules among a sample of 2,927 people incarcerated in prison. They found that greater perceptions of futurelessness were associated with a weaker commitment to follow institutional rules.…”
Section: Futurelessness and Offendingmentioning
confidence: 99%
See 3 more Smart Citations